Technological Pedagogical Content Knowledge for Arabic Teachers in Secondary School: A Design Base on Praxeological Approach - Yayan Nurbayan; Anwar Sanusi; Atifah Nabila Nurfaiza (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research explores the Technological Pedagogical Content Knowledge (TPACK) problem in Arabic language learning and how to design TPACK based on a praxeological approach for Arabic language teachers to solve issues faced by students learning Arabic in secondary school. In this context, the TPACK design, based on a praxeological approach, is ideal for solving Arabic language learning problems. This research was carried out using the Systematic Literature Review (SLR) method with data collection using the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) method regarding praxeology-based TPACK research in teaching Arabic in schools. Researchers used data sources, including journals, books, and other supporting sources, in this research. The findings in this research indicate that the main problems regarding the implementation of TPACK in Arabic language teaching are (1) the teacher's weak desire to achieve learning goals, (2) limited technological resources, and (3) the teacher's weak pedagogical competence. This problem occurs continuously because Arabic teachers need to have basic guidelines regarding the main steps to implement TPACK. Therefore, the TPACK design is based on a praxeological approach, which includes the see, act, and judge cycle and can help teachers diagnose the problems faced by students in detail. Teachers can take more directed, targeted, and practical actions when teaching Arabic.